Preschool teachers' perceptions about inclusion in preschool education: The role of experience and qualifications - Azevedo Dias, Paulo César (2018)
In Portugal, special education services were recently extended to preschool education. The studies that evaluate the perceptions of the preschool teachers about inclusive practices are also few. In this study we aim to evaluate the perceptions of preschool teachers about inclusion. A sample of 118 Portuguese preschool teachers was used. The Inclusion Inventory was administrated. The results indicate that the implementation of inclusive practices is related to perceived support and previous use of inclusive practices. Younger teachers, with less teaching experience and less time implementing inclusive practices have more beliefs about inclusion. Older professionals and teachers who spend more time working with children with special needs perceive better effects of inclusion in children. These results are discussed considering the existing literature, and implications for educational practice and research are presented.